Real-World Use of Androgen-Deprivation Therapy: Intensification Among Older Canadian Men With de Novo Metastatic Prostate Cancer. Issue 6 (1st October 2021) - Wallis, Christopher J D; Malone, Shawn; Cagiannos, Ilias; Morgan, Scott C; Hamilton, Robert J; Basappa, Naveen S; Ferrario, Cristiano; Gotto, Geoffrey T; Fernandes, Ricardo; Niazi, Tamim; Noonan, Krista L; Saad, Fred; et al.
Abstract: Background: Despite the wealth of evidence demonstrating the efficacy of treatment intensification beyond androgen-deprivation therapy (ADT) among patients with de novo metastatic castration-sensitive prostate cancer (mCSPC), little is known of its real-world use. This study examined the real-world uptake of ADT treatment intensification among older men in a large Canadian province. Methods: We performed a retrospective population-based cohort study using province-wide linked administrative data in Ontario, Canada. Patients 66 years of age and older with de novo mCSPC were included and their treatment with conventional ADT-based regimens, ADT plus next-generation androgen receptor axis–targeted therapy, and ADT plus docetaxel were identified and stratified by time. Results: From 2014 to 2019, 3556 patients were identified with de novo mCSPC. Most patients (n = 2794 [78.6%]) were treated with a conventional ADT regimen, whereas 399 (11.2%) patients received ADT intensification with docetaxel and 52 (1.5%) patients received abiraterone acetate plus prednisone. In a time-stratified analysis of ADT intensification before and after the pivotal AA+P trial (LATITUDE), AA+P uptake increased from 0.5% to 3.0%, whereas docetaxel use dropped from 12.0% to 10.0%. The median survival of the study population was 18 months (interquartile range = 10-31). Conclusions: The majority of patients with de novo mCSPC are treated with ADT alone in the Canadian real-world setting, despite randomized clinical trial evidence of benefit with the use of ADT-intensified regimens. As ADT treatment intensification is substantially underused, better understanding of the barriers to treatment and targeted education to address them are needed.